Analyze of formalin in kolang kaling (Arenga pinnata Merr) and black grass jelly (Mesona palustris BL) - Masitah Masitah; Haang Adelita; Ruqoyyah Nasution; Zenia Lutfi Kurniawati (Department of D3 Medical Technology Laboratory STIKes Hutama Abdi Husada Tulungagung, 2021)
Formalin is a chemical toxic that is abused as a food preservative and prohibited by the Indonesian government. Thus, there is a need for continuous analysis of foodstuffs that are sold in the market. When food containing formaldehyde is consumed, it will interfere with the metabolism of organs and body systems. This study aimed to analyze the presence and absence of formalin content on Kolang Kaling (Arenga pinnata Merr) and Black Grass Jelly (Mesona palustris BL) sold in Samarinda City Traditional Market, especially Segiri market, Pagi market, and Sungai Dama market. The test of formalin content was performed qualitatively using chromatophilic acid and continued quantitatively using UV-Vis spectrophotometry at the Biochemical MIPA laboratory. The results showed that 9 samples from 18 samples were identified using formalin as a preservative. The levels of formalin obtained were different, the lowest formalin level of 0.0240 mL / L in the Cincau samples (Mesona palustris BL) obtained in the Segiri market and the highest formalin level of 0.0531 mL / L in the kolang kaling sample (Arenga pinnata Merr) obtained on the Pagi market.